Damage control strategy in severe chest trauma (Revista Argentina de Cirugía, 2021)
Background: damage control surgery is a stage surgery strategy, that aims to control severe bleeding and physiological parameters in patients “in extremisˮ or exsanguinating, avoiding at the same time the installation of the deadly triad of acidosis, hypothermia and coagulopathy.Objective: to provide a strategy for damage control surgery in patients with severe thoracic trauma.Material and methods: patients with blunt and penetrating thoracic trauma during a five year study period (October 2006-September 2011).Results: of 681 patients identified, 380 (55.8%) presented with blunt trauma while 301 (44.2%) showed penetrating wounds. Of those, 140 patients underwent major surgical procedures, including 42 (6.2%) Emergency Department thoracotomies (EDT). Of these, 34 patients were male and eight female, with an average age of 25 years (range: 15-60). Of the 42 EDT, 35 (83.3%) were indicated to treat penetrating injuries (19 gunshot wounds and 16 stab wounds) and seven (16.7%) due to blunt trauma. Overall survival included six (14.3%) patients, five due to penetrating injury and one to blunt trauma.Conclusions: EDT and the early institution of damage control surgery in the chest is an essential tool as part of the armamentarium of the general surgeon trained in trauma surgery who may deal with in extremis or agonical patients on arrival.
Keywords: thoracic trauma; Emergency Department thoracotomy; exsanguination; damage control